Long-term removal increases risk aversion of a widely introduced predatory fish - Detmer, Thomas M.; Almeida, L. Zoe; Hill, Andrew A.; Ramsey, J. Wulfgar; St. John, Carl A.; Zarri, Liam; McIntyre, Peter B.; Kraft, Clifford E. (Biological invasions, 2025)
Introduced and invasive species management often focuses on active culling to limit their ecological and economic impacts, creating potential for inadvertent selection for behavioral adaptations. We compared flight initiation distance (FID), an avoidance behavior that could reduce reduced risk of capture, of introduced smallmouth bass ( Micropterus dolomieu ) and native pumpkinseed sunfish ( Lepomis gibbosus ) in three lakes, one of which has been the focus of an intensive effort to suppress smallmouth bass but not pumpkinseeds for 24 years. FID of smallmouth bass was significantly greater in the lake subject where they have been removed via boat electrofishing. In contrast, pumpkinseed sunfish exhibited no substantial variation in FID among lakes. These results suggest that our invader suppression effort may have disproportionately removed individuals with short FID, thereby selecting for smallmouth bass that are more skittish. Such evolutionary responses could reduce the effectiveness of control measures and might already have done so in our study system. This study highlights the importance of recognizing behavioral shifts in the design of control strategies for invasive or undesirable species.